Four-section approach of fetal congenital heart disease at 11–13+6 weeks - Ling, Wen; Wu, Qiumei; Guo, Shan; Li, Shangqing; Ma, Hong; Huang, Biying; Zeng, Liqin; Dang, Tingting; Liu, Min; Qiu, Xiuqing; Weng, Zongjie (Frontiers in Cardiovascular Medicine, 2023)
Objective: To explore the value of the four-section approach in detecting fetal heart defects in the first trimester (11-13 +6 weeks), analyze the reasons for the inconsistency between the results of ultrasound examination in the first trimester and subsequent verification and describe the most common abnormal flow patterns of four sections. Methods: From June 2019 to June 2021, a prenatal four-section approach (upper abdominal transverse section, four-chamber section, three vessel-trachea section and bilateral subclavian artery section) with verification results in early pregnancy was analyzed. Results: In total, 9533 cases were included. Finally, 176 cases of CHD, containing 34 types, were identified. The total detection rate of cardiac abnormalities was 1.85%. Early pregnancy and accurate diagnosis of 102 cases. There were 74 cases of inconsistent results between fetal cardiac ultrasound and verification in early pregnancy, of which 22 cases were inconsistent due to disease evolution and progression, and 52 cases were inconsistent due to missed diagnosis and misdiagnosis. The sensitivity, specificity, positive predictive value and negative predictive value of the four-section approach were 67.05%, 99.96%, 96.58% and 99.33%, respectively. In this study, a total of 30 abnormal ultrasonic imaging patterns were summarized in four sections. Conclusions: We confirmed that the four-section approach in early pregnancy has good diagnostic efficacy for fetal CHD. Intrauterine evolution of the fetal heart, missed diagnosis and misdiagnosis are the reasons for the inconsistency between the results of early pregnancy ultrasound and subsequent verification. Misdiagnosis of CHD in fetal cardiac ultrasound in the first trimester lies in defects of the fetal heart and limitations of ultrasound equipment, including insufficient subjective understanding, instrument adjustment problems or poor fetal positions. This study also presents the abnormal imaging patterns of four scan sections of CHD in early pregnancy, which are instructive for the rapid identification and diagnosis of CHD in the first trimester.